The Effectiveness of Token Economy to Reduce Truant Behavior - Samurya Rahmadhony (IJECA (International Journal of Education and Curriculum Application), 2019)
Truant is a behavior caused by a lack of control of behavior. Token economy is a form of positive renforcement where the subject receives a token when they exhibit the desired behavior. Data analysis was carried out in three stages, namely visual analysis, different tests using the Wilcoxon Signed Rank Test and calculating the effest size. Token economy interventions effectively reduce truant behavior in 5th grade elementary school students who have lived in class.